External effects of international labour migration - Мойсей, Валентина Іванівна (Technology audit and production reserves, 2015)
In the article deals with analysis approaches of native and foreign researchers to the impact of international foreign worker on economies of donors and recipients labour resources, and significantly that such an impact on the level of the world economy is positive, it contributes to the GDP. The article substantiates that at the level of national economies, this effect is ambiguous and alternate. The economy of the recipient workforce singled out such important positive effects: an increase in workforce in the economy, output growth, of the internal market; additional receipts of intellectual capital and knowledge in the economy, and others. However simultaneously previously mentioned international foreign worker leads a number of negative effects in the economy of recipient : increasing budget burden by "strong" and "local" traps unemployment; growth of shadow sector of economy; additional costs at neutralization increasing social tension and criminalization. The economy of the donor can highlight the following important positive effects of international labor migration, reducing stress on the local labor market; investment in education of potential migrants; reducing unemployment; reduce the budget burden due to unemployment benefits and other low cost. The largest negative effects in this case are "brain drain" technological lagging reducing GDP, inflation may in the case of large external benefits transfers. Developed graphical model the impact of international Labour Migration on the economies of donor and recipient workforce. A formula for determining the impact of international migration on the performance of the economy donor countries, from which you can see the change in GDP in the country – exporting workforce due to international migration.